Optimization of The Reporting and Monitoring System for Air Conditioning Maintenance at PT PPA Site SKS - Panji Setyo Nugroho (Green Publisher Indonesia, 2024)
An effective and efficient AC maintenance reporting and monitoring system is very important to ensure the smoothness and reliability of the air conditioning system. The aim of this research is to analyze the current AC maintenance reporting and monitoring system at PT PPA Site SKS. This research uses a qualitative research method with a case study approach. Data collection techniques in this research are observation and document study. The data analysis technique used in this research is qualitative analysis using the grounded theory method. The research results show that the optimization of the reporting and monitoring system for AC maintenance repoers at PT PPA Site SKS is carried out by creating inspection and maintenance schedules periodically, creating AC Number Lists and QR codes on AC units to make it easier for the PIC to input maintenance reports, accessing the AppSheet on the device each PIC is related to AC inspection and maintenance reporting, and can monitor previous maintenance history reports, appoint an Electrical Team PIC related to AC maintenance and maintenance reporting, as well as carry out socialization and coaching to the appointed PIC Admin regarding AC maintenance and maintenance reporting mechanisms via Appsheet. After being evaluated, this effort shows that AC maintenance and upkeep can be monitored 100%, and reporting is more effective (does not require admin input in every AC maintenance and maintenance report).